Konflik kerja, beban kerja dan kecenderungan stres kerja pada karyawan divisi kapal perang di PT. X - Putri, Angelika Gaby Ayu; Nurahaju, Rini; Nurcholis, Gartinia (Jurnal Psikologi Poseidon, 2024)
Abstract. This study aimed to determine the effect of work conflict and workload on the tendency of work stress independently and simultaneously on employees of the warship division at PT. X. This study utilized a quantitative approach and a survey method. The participants of this study were 58 employees of the warship division of PT X who were selected using an accidental sampling technique. The research instruments employed were the work conflict, workload, and work stress scales. The analysis technique used was multiple linear regression analysis. The results of this study indicated that there was an influence of work conflict on the tendency of work stress with a practical contribution of 65.1%, there was an influence of workload on the tendency of work stress with a practical contribution of 44.1%, and there was an influence of work conflict and workload jointly on the tendency of work stress with a practical contribution of 67.9%. The results of this study could be considered for developing psychological interventions for work stress.